Vài nét tổng quan về những tiến bộ kỹ thuật trong lĩnh vực xây dựng mạng xử lí tin quốc gia - Cát, Phạm Thượng (Journal of Computer Science and Cybernetics, 2016)
The paper deal with the evolution of computer hardware, software and maijor devices used in networking. Some methods to insulate end-users from problems are presented and finally the er gives some conclusions for the future.